IMPLENTASI PAJAK DAERAH DAN RETRIBUSI DAERAH DI ERA OTONOMI DAERAH - Tjip Ismail (Faculty of Law, Universitas Diponegoro, 2011)
The enactment of The act Number 2211999, about The Local Government and The Act Number 2511999, about The Balancing Financial between Central and Local Government, they have changed the centralization system to the decentraiization in form of giving the regional autonomy, which it's real, broad and responsible. One of the impacts of that policy is The Local Government's fiscal decentralization (financing the regional autonomy), which it is authorities to coiiect the local tax and local retribution in order to financing public services in local region. Based on the argument, they important reviewed, such as: (a) how the basic concept of the local tax and retribution tax; (b j What is the legal basis of the local tax and retribution tax; and (c) how the implementation of local tax and local retribution. The basics concepts of local tax and local retribution, its essentially, should be able to provide local revenue in accordance with the degree of fiscal autonomy period and clearly had an impact on the fiscal responsibility of owned the relevant owned. The legal basics of tax collecting, such as The Article Number 23A ofUndang- UndangDasar1945; The Article Number 7, Paragraph 4 of The Act Number 1012004, about The Establishment, Regional Regulation; The implementation of the tax collecting have to based on the principles or system, which it is called